2023
DOI: 10.1186/s12889-023-16201-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of frailty among community dweller older adults living in Gondar town, northwest, Ethiopia: a community based cross-sectional study

Abstract: Background Frailty is a multidimensional geriatric condition that increases vulnerability to stressors, increases the risk of negative health outcomes, and lowers quality of life in older people. However, little attention has been paid to frailty in developing countries, particularly in Ethiopia. Therefore, the aim of the study was to investigate the prevalence of frailty syndrome and the sociodemographic, lifestyle, and clinical factors associated with it. Method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The city is found in the Amhara regional state, approximately 747 kilometers to the northwest of Addis Ababa (the capital city of Ethiopia) and 182 kilometers from Bahir Dar. According to the Central Statistical Agency’s 2017 population projection, the city’s total population hovers around 360,600, with roughly 176,593 being males ( 36 , 37 ). The city is administratively divided into 24 ‘kebeles,’ the smallest administrative units.…”
Section: Methodsmentioning
confidence: 99%
“…The city is found in the Amhara regional state, approximately 747 kilometers to the northwest of Addis Ababa (the capital city of Ethiopia) and 182 kilometers from Bahir Dar. According to the Central Statistical Agency’s 2017 population projection, the city’s total population hovers around 360,600, with roughly 176,593 being males ( 36 , 37 ). The city is administratively divided into 24 ‘kebeles,’ the smallest administrative units.…”
Section: Methodsmentioning
confidence: 99%
“…In these areas, the primary source of care and support comes from community nurses, who play a pivotal role in their well-being. Recent research in Ethiopia revealed that a notable 39% of the senior residents in these community settings were identified as frail [24]. This high incidence of frailty among Ethiopia's older people highlights an urgent requirement for interventions and support systems to improve their health and quality of life.…”
Section: Introductionmentioning
confidence: 99%